Modified-epoxidized-polybutadiene-containing layer-adding adhesive film for FC-BGA packaging carrier plate and preparation method and application of modified-epoxidized-polybutadiene-containing layer-adding adhesive film
By using modified epoxidized polybutadiene in the reinforcing film of the FC-BGA packaging loading plate, the problems of high thermal expansion coefficient and poor flame retardant performance in the prior art are solved, and higher reliability and better flame retardant performance are achieved.
Patent Information
- Application Number
- CN202411790835.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-14
AI Technical Summary
The existing reinforcement film has problems of high thermal expansion coefficient and poor flame retardant performance in the FC-BGA packaging loading plate, which affects its reliability.
Using a layered adhesive film containing modified epoxidized polybutadiene, the phosphorus-based groups in the modified epoxidized polybutadiene are generated during combustion, which captures free radicals of the gas-phase cracking gas, reduces the thermal expansion coefficient and improves flame retardant performance.
The thermal expansion coefficient of the increase film is effectively reduced, and its flame retardant performance is improved, thereby enhancing the reliability of the FC-BGA packaging loading plate.
Smart Images

Figure BDA0005175277540000021 
Figure BDA0005175277540000031 
Figure BDA0005175277540000032
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resin composite materials, and in particular to a build-up adhesive film for an FC-BGA package carrier board containing modified epoxidized polybutadiene, and a preparation method and application thereof. Background Art
[0002] Flip chip ball grid array (FC-BGA for short) is an integrated circuit packaging technology. This packaging method inverts the chip and connects it to the packaging substrate, and then uses spherical solder joints to fix the package to the carrier. It is mainly used in the field of high-density, high-speed, and multi-functional large-scale integrated circuit chip packaging. It has the advantages of high integration, small size, high performance, and low power consumption. FC-BGA carrier is a high-density packaging carrier that can achieve high-speed and multi-functional chips. The build-up film is one of the key core materials of the semi-additive manufacturing process SAP of FC-BGA carrier.
[0003] The thermal expansion of the resin system in the existing build-up film materials will produce thermal stress. If the thermal stress is too large, it will destroy the reliability of the FC-BGA package carrier and its packaging system. In addition, the build-up film has poor flame retardant properties, resulting in a decrease in its application reliability.
[0004] Therefore, how to reduce the thermal expansion coefficient of the build-up film, ensure the reliability of the build-up film product, ensure good flame retardant properties, and improve the reliability of the build-up film product in practical applications has become a technical problem that needs to be solved urgently. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a build-up adhesive film for FC-BGA package carrier containing modified epoxidized polybutadiene, and a preparation method and application thereof, so as to solve the problem of poor flame retardant effect of the existing build-up adhesive film.
[0006] The technical solution adopted by the present invention to solve the above technical problems is as follows:
[0007] In a first aspect of the present invention, there is provided a build-up adhesive film for FC-BGA package carrier containing modified epoxidized polybutadiene, wherein the build-up adhesive film is prepared by comprising the following components in parts by weight: 45-100 parts of epoxy resin, 40-100 parts of inorganic filler, 25-45 parts of cyanate ester, 35-55 parts of bismaleimide, 5-10 parts of graphite and 10-20 parts of modified epoxidized polybutadiene;
[0008] Wherein, the preparation method of the modified epoxidized polybutadiene comprises the following steps:
[0009] Dissolving the carboxyl-terminated polybutadiene in a first organic solvent, adding a formic acid solution and a hydrogen peroxide solution, and reacting to obtain the carboxyl-terminated epoxidized polybutadiene;
[0010] The carboxyl-terminated epoxidized polybutadiene is dissolved in a first organic solvent, and (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) is added to react to obtain modified epoxidized polybutadiene.
[0011] Preferably, the graphite is amino graphite.
[0012] Preferably, the preparation method of the amino graphite is as follows:
[0013] Dispersing graphite in a mixed acid solution of concentrated sulfuric acid and nitric acid to react and obtain acidified graphite;
[0014] The acidified graphite is dissolved in a second organic solvent, and then dicyclohexylcarbodiimide, 4-dimethylaminopyridine and acrylic acid are added to react under the protection of an inert gas to obtain carboxylated graphite;
[0015] The carboxylated graphite is dissolved in a second organic solvent, and polyethylene polyamine is added thereto, and the reaction is carried out under the protection of an inert gas to obtain the amino graphite.
[0016] Preferably, the bismaleimide is silicon-containing bismaleimide;
[0017] The silicon-containing bismaleimide is selected from any one of silicon-containing bismaleimide I, silicon-containing bismaleimide II, and silicon-containing bismaleimide III, or a combination of at least two thereof;
[0018] Wherein, the structural formula of the silicon-containing bismaleimide I is:
[0019]
[0020] The structural formula of the silicon-containing bismaleimide II is:
[0021]
[0022] The structural formula of the silicon-containing bismaleimide III is:
[0023]
[0024] Preferably, the cyanate ester is a boron-containing cyanate ester.
[0025] Preferably, the preparation method of the boron cyanate ester is as follows:
[0026] Cyanogen bromide is dissolved in a third organic solvent, and triethylamine and 1,2-di(4-hydroxyphenyl)-o-dicarbon-substituted closed dodecaborane are added to react to obtain the boron-containing cyanate.
[0027] Preferably, the epoxy resin is selected from any one or a combination of at least two of bisphenol epoxy resin, biphenyl epoxy resin, naphthalene epoxy resin, naphthol epoxy resin, linear phenolic epoxy resin, dicyclopentadiene epoxy resin, aralkyl phenolic epoxy resin, aralkyl biphenyl phenolic epoxy resin or naphthol phenolic epoxy resin;
[0028] The inorganic filler is selected from any one of silicon dioxide, aluminum oxide, glass, cordierite, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate, calcium zirconate or zirconium phosphate, or a combination of at least two thereof.
[0029] Preferably, the build-up adhesive film further comprises 0.2-0.5 parts of a curing accelerator;
[0030] The curing accelerator is selected from any one of 1-cyanoethyl-2-ethyl-4-methylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2-ethyl-4-methylimidazole, and 4-dimethylaminopyridine, or a combination of at least two thereof.
[0031] The second aspect of the present invention provides a method for preparing a build-up adhesive film for FC-BGA package carrier containing modified epoxidized polybutadiene, the preparation method comprising the following steps:
[0032] The components of the build-up adhesive film are mixed evenly, coated on a substrate, and dried to obtain the build-up adhesive film.
[0033] The third aspect of the present invention provides the use of the above-mentioned build-up adhesive film for FC-BGA package carrier containing modified epoxidized polybutadiene in FC-BGA package carrier.
[0034] Beneficial effects:
[0035] The invention discloses a build-up adhesive film for an FC-BGA package carrier board containing modified epoxidized polybutadiene, and a preparation method and application thereof. The invention modifies the epoxidized polybutadiene, and the modified epoxidized polybutadiene contains phosphorus-based groups. When burned, the phosphorus-based groups generate phosphaphenanthrene groups in the gas phase, which can capture free radicals of gas-phase cracking gas to form a stable structure, exert a free radical quenching effect, and improve the flame retardant efficiency of the build-up adhesive film. DETAILED DESCRIPTION
[0036] The present invention provides a build-up adhesive film for FC-BGA package carrier containing modified epoxidized polybutadiene and a preparation method and application thereof. In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0037] The embodiment of the present invention provides a build-up adhesive film for FC-BGA package carrier containing modified epoxidized polybutadiene, wherein the build-up adhesive film is prepared by comprising the following components in parts by weight: 45-100 parts of epoxy resin, 40-100 parts of inorganic filler, 25-45 parts of cyanate ester, 35-55 parts of bismaleimide, 5-10 parts of graphite and 10-20 parts of modified epoxidized polybutadiene;
[0038] Wherein, the preparation method of the modified epoxidized polybutadiene comprises the following steps:
[0039] Dissolving the carboxyl-terminated polybutadiene in a first organic solvent, adding a formic acid solution and a hydrogen peroxide solution, and reacting to obtain the carboxyl-terminated epoxidized polybutadiene;
[0040] The carboxyl-terminated epoxidized polybutadiene is dissolved in a first organic solvent, and (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) is added to react to obtain modified epoxidized polybutadiene.
[0041] The embodiment of the present invention modifies the epoxidized polybutadiene, and the modified epoxidized polybutadiene contains phosphorus-based groups. When burned, the phosphorus-based groups will generate phosphaphenanthrene groups in the gas phase, which can capture free radicals of gas-phase cracking gases to form a stable structure, exert a free radical quenching effect, and improve the flame retardant efficiency of the build-up film.
[0042] In some embodiments, the first organic solvent is selected from one or more of toluene, xylene, dichloromethane, and chloroform.
[0043] In some embodiments, the method for preparing the modified epoxidized polybutadiene comprises the following steps:
[0044] Dissolve 10 parts of carboxyl-terminated polybutadiene in 300 parts of toluene, stir at 90°C for 0.5h, cool to 40°C after complete dissolution, add 3 parts of 80% by mass formic acid solution and 6 parts of 30% by mass hydrogen peroxide solution, stir and react at 30°C for 12h to obtain a reaction solution; add deionized water to separate formic acid and hydrogen peroxide in the reaction solution, repeat several times until the pH of the reaction solution is 6.8, then add 500 parts of anhydrous ethanol to the reaction solution, dry the precipitated product, and obtain carboxyl-terminated epoxidized polybutadiene;
[0045] Dissolve 20 parts of terminal carboxyl epoxidized polybutadiene in 200 parts of toluene, stir at 90°C for 0.5h, add 15 parts of (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) after complete dissolution, stir and react at 120°C for 12h, separate the solid product and toluene by rotary evaporator after the reaction is completed, and the solid product is the modified epoxidized polybutadiene after drying.
[0046] In some embodiments, the weight percentage of the epoxy resin may be 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, 95 parts, 100 parts;
[0047] The weight proportion of the inorganic filler can be 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, 95 parts, 100 parts;
[0048] The weight proportions of the cyanate ester may be 25 parts, 30 parts, 35 parts, 40 parts, or 45 parts;
[0049] The weight proportions of the bismaleimide can be 35 parts, 40 parts, 45 parts, 50 parts, or 55 parts;
[0050] The weight proportions of the graphite can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, or 10 parts;
[0051] The weight proportions of the modified epoxidized polybutadiene can be 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, or 20 parts.
[0052] In some embodiments, the graphite is amino graphite.
[0053] The amino groups in the aminated graphite can react with the carboxyl groups in the modified epoxidized polybutadiene to form a graphite / resin interface region, which has a strong restraining ability on dipole polarization and can reduce the loss caused by dipole polarization, thereby reducing the dielectric loss of the system; in addition, after the aminated graphite reacts with the modified epoxidized polybutadiene, the packing density of the molecular chains can be increased. The denser the packing, the smaller the free volume, and the movement space of the resin molecular chain segments is limited, thereby obtaining a reduced thermal expansion coefficient.
[0054] Specifically, the embodiment of the present invention reacts the carboxyl group of modified epoxidized polybutadiene with the amino group of amino graphite to build an interpenetrating network structure, restrict the movement of epoxy resin molecular segments, and reduce the thermal expansion coefficient of the system. The interpenetrating network structure has high symmetry. When the frequency increases or decreases, the interpenetrating network structure is insensitive to polarization relaxation, and its dielectric constant and dielectric loss factor do not change significantly, thereby achieving low dielectric loss of the film.
[0055] In some embodiments, the preparation method of the amino graphite is as follows:
[0056] Dispersing graphite in a mixed acid solution of concentrated sulfuric acid and nitric acid to react and obtain acidified graphite;
[0057] The acidified graphite is dissolved in a second organic solvent, and then dicyclohexylcarbodiimide, 4-dimethylaminopyridine and acrylic acid are added to react under the protection of an inert gas to obtain carboxylated graphite;
[0058] The carboxylated graphite is dissolved in a second organic solvent, and polyethylene polyamine is added thereto, and the reaction is carried out under the protection of an inert gas to obtain the amino graphite.
[0059] The graphite is dispersed in a mixed acid solution of concentrated sulfuric acid and nitric acid, wherein the concentrated sulfuric acid is used as a dehydrating agent and the concentrated nitric acid provides a nitro group, thereby obtaining acidified graphite; under the joint action of dicyclohexylcarbodiimide, 4-dimethylaminopyridine and acrylic acid, the carboxyl group in the acrylic acid molecule is introduced into the graphite to form carboxylated graphite; the carboxylated graphite is reacted with polyethylene polyamine through an amidation reaction to introduce an amino group into the graphite structure, thereby obtaining aminoated graphite.
[0060] In some embodiments, the second organic solvent is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and tetrahydrofuran.
[0061] In some embodiments, the preparation method of the amino graphite is: weigh 5 parts of graphite and disperse it in a mixed acid solution of 20 parts of concentrated sulfuric acid and 30 parts of nitric acid, ultrasonically disperse it at a power of 800 W for 1 hour, then heat reflux at 160° C. for 1.5 hours, wash the product with distilled water for multiple times until it is neutral, filter it, and dry it to obtain acidified graphite;
[0062] Weigh 1 part of acidified graphite and disperse it in 100 parts of N,N-dimethylformamide, and perform ultrasonic dispersion for 0.5 h at a power of 600 W to obtain a suspension, add 4 parts of dicyclohexylcarbodiimide, 0.4 parts of 4-dimethylaminopyridine, and 10 parts of acrylic acid to the suspension, react at 90° C. for 20 h under nitrogen atmosphere protection, wash, filter, and dry to obtain carboxylated graphite;
[0063] Weigh 5 parts of carboxylated graphite and disperse them in 100 parts of N,N-dimethylformamide, and ultrasonically disperse them at a power of 500 W for 1 hour. Then add 4 parts of polyethylene polyamine, react at room temperature for 0.5 hour in a nitrogen atmosphere, wash, filter, and dry to obtain amino graphite.
[0064] In some embodiments, the bismaleimide is a silicon-containing bismaleimide;
[0065] The silicon-containing bismaleimide is selected from any one of silicon-containing bismaleimide I, silicon-containing bismaleimide II, and silicon-containing bismaleimide III, or a combination of at least two thereof;
[0066] Wherein, the structural formula of the silicon-containing bismaleimide I is:
[0067]
[0068] The structural formula of the silicon-containing bismaleimide II is:
[0069]
[0070] The structural formula of the silicon-containing bismaleimide III is:
[0071]
[0072] It should be noted that the examples of the present invention do not impose any special restrictions on the source of silicon-containing bismaleimide, which can be purchased from the market or prepared by itself. The examples of the present invention do not impose any special restrictions on the preparation method thereof. For example, reference may be made to the preparation methods described in “Tang H, Song N, Chen X, et al. Synthesis and properties of silicon-containing bismaleimide resins [J]. Journal of Applied Polymer Science, 2010, 109 (1): 190-199.” and “Wei-Jye, Shu, Ruey-Shi, et al. Studies of Silicon-Containing Bismaleimide Resins. Part I: Synthesis and Characteristics of Model Compounds and Polyaspartimides [J]. Designed Monomers & Polymers, 2010.”
[0073] Specifically, silicon-containing bismaleimides I, II, and III contain large functional groups such as benzene rings with large molar volumes. Such large functional groups can limit the movement of polymer chain segments and reduce the degree of polarization, thereby effectively reducing the dielectric constant and dielectric loss of the build-up film. In addition, the decomposition of silicon elements in silicon-containing bismaleimides I, II, and III will generate an oxide carbon layer. The oxide carbon layer can prevent the escape of volatile substances generated by the combustion of the material, isolate oxygen from contact with the resin, and prevent the melt from dripping, thereby achieving the purpose of flame retardancy.
[0074] In some embodiments, the cyanate ester is a boron-containing cyanate ester.
[0075] The boron element in the boron cyanate ester decomposes under heat to produce boric anhydride or boric acid, which will form a glassy melt that covers the surface of the build-up film, isolating the spread of oxygen and heat, inhibiting the generation of thick smoke and molten droplets, and improving the flame retardant properties of the build-up film.
[0076] In addition, the metaphosphoric acid generated by the decomposition of the phosphorus-containing groups of the modified epoxidized polybutadiene of the present invention removes water in the base material to form a phosphorus-containing carbon layer. The silicon element of the silicon-containing bismaleimide has a low surface energy and is easy to migrate to the surface of the base material to form a silicon-containing protective layer, thereby improving the thermal stability of the phosphorus-containing carbon layer on the surface of the base material and inhibiting the oxidation of the phosphorus-containing carbon layer under high temperature conditions. The boron element of the boron cyanate ester can form a porous carbon layer with a ceramic structure at high temperature, which is beneficial to heat insulation and preventing air from diffusing into the interior of the material. The synergistic flame retardancy is achieved through the combined action of the phosphorus-boron-silicon elements.
[0077] In some embodiments, the preparation method of the boron cyanate ester is as follows:
[0078] Cyanogen bromide is dissolved in a third organic solvent, and triethylamine and 1,2-di(4-hydroxyphenyl)-o-dicarbon-substituted closed dodecaborane are added to react to obtain the boron-containing cyanate.
[0079] The hydroxyl group in 1,2-bis(4-hydroxyphenyl)-o-dicarbonyl closed dodecaborane is a nucleophilic center, and the hydroxyl oxygen atom can attack the carbon atom in cyanogen bromide to form an intermediate, which is subsequently deprotonated by triethylamine to obtain a boron-containing cyanate.
[0080] In some embodiments, the third organic solvent is selected from one or more of butanone, acetone, and cyclohexanone.
[0081] In some embodiments, the preparation method of the boron-containing cyanate is: dissolving 10 parts of cyanogen bromide in 50 parts of butanone, stirring evenly at 0°C, adding 20 parts of triethylamine and 10 parts of 1,2-bis(4-hydroxyphenyl)-o-dicarbon-substituted closed dodecaborane, reacting at 5°C for 2h, filtering and distilling under reduced pressure to obtain a product, recrystallizing the product with isopropanol, and vacuum drying to obtain the boron-containing cyanate.
[0082] In some embodiments, the epoxy resin is selected from any one or a combination of at least two of bisphenol epoxy resin, biphenyl epoxy resin, naphthalene epoxy resin, naphthol epoxy resin, linear phenolic epoxy resin, dicyclopentadiene epoxy resin, aralkyl phenolic epoxy resin, aralkyl biphenyl phenolic epoxy resin or naphthol phenolic epoxy resin;
[0083] The inorganic filler is selected from any one of silicon dioxide, aluminum oxide, glass, cordierite, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate, calcium zirconate or zirconium phosphate, or a combination of at least two thereof.
[0084] In some embodiments, the build-up adhesive film further comprises 0.2-0.5 parts by weight of a curing accelerator;
[0085] The curing accelerator is selected from any one of 1-cyanoethyl-2-ethyl-4-methylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2-ethyl-4-methylimidazole, and 4-dimethylaminopyridine, or a combination of at least two thereof.
[0086] In some embodiments, the weight percentage of the curing accelerator may be 0.1 part, 0.2 part, 0.3 part, 0.4 part, or 0.5 part.
[0087] In some embodiments, the build-up adhesive film further comprises 200-300 parts by weight of a component organic solvent;
[0088] The component organic solvent is selected from any one of toluene, xylene, butanone, methyl ethyl ketone, cyclohexanone, ethyl acetate or N,N-dimethylformamide, or a combination of at least two thereof.
[0089] In some embodiments, the weight parts of the component organic solvent can be 200 parts, 210 parts, 220 parts, 230 parts, 240 parts, 250 parts, 260 parts, 270 parts, 280 parts, 290 parts, or 300 parts.
[0090] In some embodiments, the build-up adhesive film has a thickness of 10-100 μm.
[0091] In some preferred embodiments, the build-up adhesive film has a thickness of 25-50 μm.
[0092] The embodiment of the present invention provides a method for preparing the above-mentioned build-up adhesive film for FC-BGA package carrier containing modified epoxidized polybutadiene, and the preparation method comprises the following steps:
[0093] The components of the build-up adhesive film are mixed evenly, coated on a substrate, and dried to obtain the build-up adhesive film.
[0094] Wherein, the drying temperature is 80-130° C., and the drying time is 3-10 min.
[0095] The drying temperature can be 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, or 130°C; the drying time can be 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, or 10 min.
[0096] In some embodiments, the drying step further includes a post-treatment step: the post-treatment method is to remove the substrate.
[0097] It should be noted that the embodiments of the present invention do not specifically limit the selection of the substrate, and any substrate commonly used in the art can be used, including but not limited to: PET release film, polyethylene film, polypropylene film or polyvinyl chloride film. At the same time, in order to facilitate the subsequent removal of the substrate, the polyethylene film, polypropylene film or polyvinyl chloride film can be corona treated in advance before use.
[0098] In some embodiments, the present invention provides the use of the above-mentioned build-up adhesive film for FC-BGA package carrier containing modified epoxidized polybutadiene in FC-BGA package carrier.
[0099] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments, and are only for illustrating the present invention but not limiting the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0100] The sources of some components in the examples and comparative examples of the present invention are as follows:
[0101] Epoxy resin: naphthalene type epoxy resin ("HP-6000" manufactured by DIC Corporation of Japan);
[0102] Inorganic filler: silicon dioxide (“SO-C2” manufactured by Yaduma Corporation);
[0103] Cyanate ester: commercially available cyanate ester ("BA230S75" manufactured by Lonza Japan);
[0104] Bismaleimide: commercially available bismaleimide ("BMI5100" manufactured by Yamato Chemical Industries, Ltd., Japan);
[0105] Graphite: commercially available graphite, CAS number: 7782-42-5;
[0106] Curing accelerator: 4-dimethylaminopyridine (DMAP), CAS No.: 1122-58-3.
[0107] Preparation Example 1
[0108] The preparation of boron-containing cyanate comprises the following steps: dissolving 10 parts of cyanogen bromide in 50 parts of butanone, stirring evenly at 0°C, adding 20 parts of triethylamine and 10 parts of 1,2-di(4-hydroxyphenyl)-o-dicarbon-substituted closed dodecaborane, reacting at 5°C for 2h, filtering and distilling under reduced pressure to obtain a product, recrystallizing the product with isopropanol, and vacuum drying to obtain the boron-containing cyanate.
[0109] Note: The boron-containing cyanate esters used in the following examples or comparative examples are all the boron-containing cyanate esters prepared in Preparation Example 1.
[0110] Preparation Example 2
[0111] The preparation of modified epoxidized polybutadiene comprises the following steps: dissolving 10 parts of carboxyl-terminated polybutadiene in 300 parts of toluene, stirring at 90°C for 0.5h, cooling to 40°C after complete dissolution, adding 3 parts of formic acid solution with a mass concentration of 80% and 6 parts of hydrogen peroxide solution with a mass concentration of 30%, stirring and reacting at 30°C for 12h to obtain a reaction solution; adding deionized water to separate formic acid and hydrogen peroxide in the reaction solution, repeating the process several times until the pH value of the reaction solution is 6.8, then adding 500 parts of anhydrous ethanol to the reaction solution, drying the precipitated product, and obtaining carboxyl-terminated epoxidized polybutadiene;
[0112] Dissolve 20 parts of terminal carboxyl epoxidized polybutadiene in 200 parts of toluene, stir at 90°C for 0.5h, add 15 parts of (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) after complete dissolution, stir and react at 120°C for 12h, separate the solid product and toluene by rotary evaporator after the reaction is completed, and the solid product is the modified epoxidized polybutadiene after drying.
[0113] Note: The modified epoxidized polybutadiene used in the following examples or comparative examples is the modified epoxidized polybutadiene prepared in Preparation Example 2.
[0114] Preparation Example 3
[0115] The preparation of amino graphite comprises the following steps: weighing 5 parts of graphite and dispersing it in a mixed acid solution of 20 parts of concentrated sulfuric acid and 30 parts of nitric acid, ultrasonically dispersing it for 1 hour at a power of 800 W, then refluxing it at 160° C. for 1.5 hours, washing the product with distilled water for multiple times until it is neutral, filtering it, and drying it to obtain acidified graphite;
[0116] Weigh 1 part of acidified graphite and disperse it in 100 parts of N,N-dimethylformamide, and perform ultrasonic dispersion for 0.5 h at a power of 600 W to obtain a suspension, add 4 parts of dicyclohexylcarbodiimide, 0.4 parts of 4-dimethylaminopyridine, and 10 parts of acrylic acid to the suspension, react at 90° C. for 20 h under nitrogen atmosphere protection, wash, filter, and dry to obtain carboxylated graphite;
[0117] Weigh 5 parts of carboxylated graphite and disperse them in 100 parts of N,N-dimethylformamide, and ultrasonically disperse them at a power of 500 W for 1 hour. Then add 4 parts of polyethylene polyamine, react at room temperature for 0.5 hour in a nitrogen atmosphere, wash, filter, and dry to obtain amino graphite.
[0118] Note: The aminated graphite used in the following examples or comparative examples is the aminated graphite prepared in Preparation Example 3.
[0119] Example 1
[0120] This embodiment provides a build-up adhesive film for FC-BGA package carrier containing modified epoxidized polybutadiene. The raw materials of the build-up adhesive film include, by weight:
[0121] 100 parts of naphthalene epoxy resin (HP-6000), 100 parts of spherical silica (SO-C2), 45 parts of boron cyanate, 55 parts of silicon-containing bismaleimide II, 20 parts of modified epoxidized polybutadiene, 10 parts of amino graphite, 0.5 parts of 4-dimethylaminopyridine (DMAP) and 300 parts of cyclohexanone.
[0122] The preparation method of the build-up adhesive film is as follows: after uniformly mixing the raw material components according to the above proportions, coating the mixture on a PET release film, drying at 80° C. for 10 min, removing the PET release film, and obtaining a build-up adhesive film with a thickness of 100 μm.
[0123] Example 2
[0124] This embodiment provides a build-up adhesive film for FC-BGA package carrier containing modified epoxidized polybutadiene. The raw materials of the build-up adhesive film include, by weight:
[0125] 45 parts of naphthalene epoxy resin (HP-6000), 40 parts of spherical silica (SO-C2), 25 parts of boron cyanate, 35 parts of silicon-containing bismaleimide I, 10 parts of modified epoxidized polybutadiene, 5 parts of amino graphite, 0.2 parts of 4-dimethylaminopyridine (DMAP) and 200 parts of cyclohexanone.
[0126] The preparation method of the build-up adhesive film is as follows: after uniformly mixing the raw material components according to the above proportions, coating the mixture on a PET release film, drying at 130° C. for 3 minutes, removing the PET release film, and obtaining a build-up adhesive film with a thickness of 10 μm.
[0127] Example 3
[0128] This embodiment provides a build-up adhesive film for FC-BGA package carrier containing modified epoxidized polybutadiene. The raw materials of the build-up adhesive film include, by weight:
[0129] 80 parts of naphthalene epoxy resin (HP-6000), 60 parts of spherical silica (SO-C2), 30 parts of boron cyanate, 40 parts of silicon-containing bismaleimide III, 15 parts of modified epoxidized polybutadiene, 8 parts of amino graphite, 0.4 parts of 4-dimethylaminopyridine (DMAP) and 250 parts of cyclohexanone.
[0130] The preparation method of the build-up adhesive film is as follows: after uniformly mixing the raw material components according to the above proportions, coating the mixture on a PET release film, drying at 110° C. for 5 minutes, removing the PET release film, and obtaining a build-up adhesive film with a thickness of 40 μm.
[0131] Comparative Example 1
[0132] This comparative example provides a build-up adhesive film, and the raw materials of the build-up adhesive film include, by weight:
[0133] 100 parts of naphthalene epoxy resin (HP-6000), 40 parts of spherical silica (SO-C2), 45 parts of cyanate (BA230S), 55 parts of bismaleimide (BMI5100), 10 parts of graphite, 0.2 parts of 4-dimethylaminopyridine (DMAP) and 300 parts of cyclohexanone.
[0134] The preparation method of the build-up adhesive film is as follows: after uniformly mixing the raw material components according to the above proportions, coating the mixture on a PET release film, drying at 80° C. for 10 min, removing the PET release film, and obtaining a build-up adhesive film with a thickness of 100 μm.
[0135] Comparative Example 2
[0136] This comparative example provides a build-up adhesive film, and the raw materials of the build-up adhesive film include, by weight:
[0137] 100 parts of naphthalene epoxy resin (HP-6000), 40 parts of spherical silica (SO-C2), 30 parts of boron cyanate, 55 parts of bismaleimide (BMI5100), 10 parts of graphite, 0.2 parts of 4-dimethylaminopyridine (DMAP) and 300 parts of cyclohexanone.
[0138] The preparation method of the build-up adhesive film is as follows: after uniformly mixing the raw material components according to the above proportions, coating the mixture on a PET release film, drying at 80° C. for 10 min, removing the PET release film, and obtaining a build-up adhesive film with a thickness of 100 μm.
[0139] Comparative Example 3
[0140] This comparative example provides a build-up adhesive film, and the raw materials of the build-up adhesive film include, by weight:
[0141] 100 parts of naphthalene epoxy resin (HP-6000), 40 parts of spherical silica (SO-C2), 45 parts of cyanate (BA230S), 55 parts of silicon-containing bismaleimide, 10 parts of graphite, 0.2 parts of 4-dimethylaminopyridine (DMAP) and 300 parts of cyclohexanone.
[0142] The preparation method of the build-up adhesive film is as follows: after uniformly mixing the raw material components according to the above proportions, coating the mixture on a PET release film, drying at 80° C. for 10 min, removing the PET release film, and obtaining a build-up adhesive film with a thickness of 100 μm.
[0143] Comparative Example 4
[0144] This comparative example provides a build-up adhesive film, and the raw materials of the build-up adhesive film include, by weight:
[0145] 100 parts of naphthalene epoxy resin (HP-6000), 40 parts of spherical silica (SO-C2), 45 parts of cyanate (BA230S), 55 parts of bismaleimide (BMI5100), 20 parts of modified epoxidized polybutadiene, 10 parts of graphite, 0.2 parts of 4-dimethylaminopyridine (DMAP) and 300 parts of cyclohexanone.
[0146] The preparation method of the build-up adhesive film is as follows: after uniformly mixing the raw material components according to the above proportions, coating the mixture on a PET release film, drying at 80° C. for 10 min, removing the PET release film, and obtaining a build-up adhesive film with a thickness of 100 μm.
[0147] Comparative Example 5
[0148] This comparative example provides a build-up adhesive film, and the raw materials of the build-up adhesive film include, by weight:
[0149] 100 parts of naphthalene epoxy resin (HP-6000), 40 parts of spherical silica (SOC2), 45 parts of cyanate (BA230S), 55 parts of bismaleimide (BMI5100), 10 parts of amino graphite, 0.2 parts of 4-dimethylaminopyridine (DMAP) and 300 parts of cyclohexanone.
[0150] The preparation method of the build-up adhesive film is as follows: after uniformly mixing the raw material components according to the above proportions, coating the mixture on a PET release film, drying at 80° C. for 10 min, removing the PET release film, and obtaining a build-up adhesive film with a thickness of 100 μm.
[0151] The performance of the build-up adhesive films provided in the above embodiments and comparative examples was tested, and the testing method was as follows:
[0152] Thermal expansion coefficient: The build-up adhesive film with PET release film prepared in the above embodiments and comparative examples was cured at 100°C for 30 min and at 190°C for 90 min, and then the release film was peeled off to obtain a test sample; the test sample was cut into test pieces with a width of about 3 mm and a length of about 20 mm, and a thermal mechanical analysis was performed using a thermomechanical analysis device ("TMA450" from TA Company, USA) under the conditions of a preload force of 0.02 N, a heating range of 25°C-260°C, and a heating rate of 10°C / min, to obtain a thermal expansion coefficient in the range of 150°C to 240°C.
[0153] Flame retardancy: The build-up adhesive film with PET release film prepared in the above examples and comparative examples was pressed with a substrate (MCL-E-705G of Hitachi Chemical, Japan) by a film laminating machine, and the build-up adhesive film (the side without PET release film) was pressed on both sides of the substrate to obtain a laminate; after the lamination was completed, the PET release film on the laminate was removed, and the build-up adhesive film was thermally cured (cured at 190°C for 90 minutes) to form a cured product on both sides of the substrate. The laminate (thickness of about 380μm) was cut into samples of 12.7mm×127mm in size and 1.27mm in edge size, and tested according to the UL-94V standard, and the test results were recorded.
[0154] Dielectric loss tangent: The build-up film with PET release film prepared in the above-mentioned embodiments and comparative examples was cured at 100°C for 30 min and at 190°C for 90 min, and then the release film was peeled off to obtain a pre-cured build-up film; the pre-cured build-up film was cut into 80mm×80mm test pieces (3 pieces), and then the dielectric loss tangent of each test piece was measured by cavity resonance perturbation method at a measurement frequency of 5.8 GHz and a measurement temperature of 23°C using "HP8362B" of Agilent Technologies Inc., and the average value of the three test pieces was calculated as the dielectric loss tangent.
[0155] The performance test results of the build-up adhesive films provided in the examples and comparative examples are shown in Table 1:
[0156] Table 1
[0157]
[0158]
[0159] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A build-up adhesive film for FC-BGA package carrier containing modified epoxidized polybutadiene, characterized in that: The build-up adhesive film is prepared by comprising the following components in parts by weight: 45-100 parts of epoxy resin, 40-100 parts of inorganic filler, 25-45 parts of cyanate ester, 35-55 parts of bismaleimide, 5-10 parts of graphite and 10-20 parts of modified epoxidized polybutadiene; Wherein, the preparation method of the modified epoxidized polybutadiene comprises the following steps: Dissolving the carboxyl-terminated polybutadiene in a first organic solvent, adding a formic acid solution and a hydrogen peroxide solution, and reacting to obtain the carboxyl-terminated epoxidized polybutadiene; The carboxyl-terminated epoxidized polybutadiene is dissolved in a first organic solvent, and (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) is added to react to obtain modified epoxidized polybutadiene.
2. The build-up adhesive film for FC-BGA package carrier containing modified epoxidized polybutadiene according to claim 1, characterized in that: The graphite is amino graphite.
3. The build-up adhesive film for FC-BGA package carrier containing modified epoxidized polybutadiene according to claim 2, characterized in that: The preparation method of the amino graphite is as follows: Dispersing graphite in a mixed acid solution of concentrated sulfuric acid and nitric acid to react and obtain acidified graphite; The acidified graphite is dissolved in a second organic solvent, and then dicyclohexylcarbodiimide, 4-dimethylaminopyridine and acrylic acid are added to react under the protection of an inert gas to obtain carboxylated graphite; The carboxylated graphite is dissolved in a second organic solvent, and polyethylene polyamine is added thereto, and the reaction is carried out under the protection of an inert gas to obtain the amino graphite.
4. The build-up adhesive film for FC-BGA package carrier containing modified epoxidized polybutadiene according to claim 1, characterized in that: The bismaleimide is silicon-containing bismaleimide; The silicon-containing bismaleimide is selected from any one of silicon-containing bismaleimide I, silicon-containing bismaleimide II, and silicon-containing bismaleimide III, or a combination of at least two thereof; Wherein, the structural formula of the silicon-containing bismaleimide I is: The structural formula of the silicon-containing bismaleimide II is: The structural formula of the silicon-containing bismaleimide III is:
5. The build-up adhesive film for FC-BGA package carrier containing modified epoxidized polybutadiene according to claim 1, characterized in that: The cyanate ester is a boron-containing cyanate ester.
6. The build-up adhesive film for FC-BGA package carrier containing modified epoxidized polybutadiene according to claim 5, characterized in that: The preparation method of the boron cyanate ester is as follows: Cyanogen bromide is dissolved in a third organic solvent, and triethylamine and 1,2-di(4-hydroxyphenyl)-o-dicarbon-substituted closed dodecaborane are added to react to obtain the boron-containing cyanate.
7. The build-up adhesive film for FC-BGA package carrier containing modified epoxidized polybutadiene according to claim 1, characterized in that: The epoxy resin is selected from any one or a combination of at least two of bisphenol epoxy resin, biphenyl epoxy resin, naphthalene epoxy resin, naphthol epoxy resin, linear phenolic epoxy resin, dicyclopentadiene epoxy resin, aralkyl phenolic epoxy resin, aralkyl biphenyl phenolic epoxy resin or naphthol phenolic epoxy resin; The inorganic filler is selected from any one of silicon dioxide, aluminum oxide, glass, cordierite, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate, calcium zirconate or zirconium phosphate, or a combination of at least two thereof.
8. The build-up adhesive film for FC-BGA package carrier containing modified epoxidized polybutadiene according to claim 1, characterized in that: The build-up adhesive film further includes 0.2-0.5 parts of a curing accelerator; The curing accelerator is selected from any one of 1-cyanoethyl-2-ethyl-4-methylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2-ethyl-4-methylimidazole, and 4-dimethylaminopyridine, or a combination of at least two thereof.
9. A method for preparing a build-up adhesive film for FC-BGA package carrier containing modified epoxidized polybutadiene according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: The components of the build-up adhesive film are mixed evenly, coated on a substrate, and dried to obtain the build-up adhesive film.
10. Use of the build-up adhesive film for FC-BGA package carrier containing modified epoxidized polybutadiene as claimed in any one of claims 1 to 8 in FC-BGA package carrier.
Citation Information
Cited By
Modified epoxidized polybutadiene-containing build-up film for FC-BGA packaging substrate, preparation method therefor and use thereof
WO2026118494A1